Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2337/db06-0419
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Automating Insulin Delivery for the Treatment of Type 1 Diabetes

Abstract: O ptimal treatment of type 1 diabetes should achieve normoglycemia at all times, without risk of hypoglycemia. Such a treatment should dramatically reduce or prevent diabetes complications and significantly improve patients' quality of life. This goal may be accomplished through pancreatic or islet cell transplantation, but availability of these tissues is limited, survival and function are unpredictable, and longterm immunosuppressive therapy is required (1). The potential for an automated closed-loop system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
330
1
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 429 publications
(368 citation statements)
references
References 27 publications
5
330
1
20
Order By: Relevance
“…Peak postprandial glucose levels declined from ~250 to 180 mg/dl, and levels 3-4 h postprandial became more stable. Meal responses obtained with MPC by teams comprising investigators at the University of Virginia and Padova and at Boston University and Massachusetts General Hospital [13][14][15][16] (Figure 1B) generally showed the peak breakfast response to be similar to the initial PID study 2 . Still, comparing meal responses across studies can be confounded by differences in meal size, and averaging data inevitably results in peak postprandial values lower than the average of individual peak values.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Peak postprandial glucose levels declined from ~250 to 180 mg/dl, and levels 3-4 h postprandial became more stable. Meal responses obtained with MPC by teams comprising investigators at the University of Virginia and Padova and at Boston University and Massachusetts General Hospital [13][14][15][16] (Figure 1B) generally showed the peak breakfast response to be similar to the initial PID study 2 . Still, comparing meal responses across studies can be confounded by differences in meal size, and averaging data inevitably results in peak postprandial values lower than the average of individual peak values.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
“…The group at Boston University/Massachusetts General Hospital has advocated the use of glucagon throughout development of their MPC algorithm, 15,16 whereas the PID algorithm developed at Medtronic, [2][3][4] and variations evaluated at Boston Children's Hospital/Joslin Diabetes Center, 5,6 have been developed for use with insulin alone. The use of glucagon is not strictly speaking an MPC versus PID question, as glucagon can be used with PID control.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Two main categories of control algorithms have been employed, the proportional-integral-derivative (PID) controller [48,49], and the model predictive controller (MPC) [50]. Other approaches include controllers based on fuzzy logic (‘MD logic’) [51] or a combination of MPC and PID for insulin and glucagon codelivery [52].…”
Section: Glucose Responsive Suspension Of Insulin Deliverymentioning
confidence: 99%
“…A variety of PID control strategies have been developed for diabetes and described in survey papers and articles [7][8][9]11,[37][38][39]. Most of the related evaluations have been based on simulation studies but experimental applications to dogs and humans have also been reported.…”
Section: A Pid Switching Control Strategymentioning
confidence: 99%